Towards an understanding of sex differences in functional outcome following moderate to severe traumatic brain injury: a systematic review. Issue 11 (21st October 2008) - Slewa-Younan, S; van den Berg, S; Baguley, I J; Nott, M; Cameron, I D
Abstract : Background and aim: A clear understanding of the impact sex differences play in clinical traumatic brain injury (TBI) outcome remains elusive. Animal research suggests that females have better functional outcomes following TBI than males. Therefore, this paper aims to systematically review all studies that have examined sex differences in functional outcome measures following moderate to severe TBI in humans. It was predicted that women would exhibit better functional outcome than men. Methods: A predefined study selection criteria was adopted to screen studies eligible for inclusion. A comprehensive and systematic search of various databases, up to the end of April 2007, was undertaken. Two independent reviewers screened studies for eligibility. Selected studies were assessed for methodological quality. Results: 13 studies were included. Because of the heterogeneity of the functional outcome measures and lack of appropriate statistical information, a qualitative analysis was performed. More than half of the papers were considered high quality. Strong evidence was found to suggest that women do not have better functional outcome than men following moderate to severe TBI. Conclusion: The results of this review are contrary to the suggestions from animal literature. Consideration of factors such as the woman patient's hormonal status at the time of injury and other sources of heterogeneity such as age and injury severity should be addressed in future prospective studies.